Pengembangan Aplikasi Android sebagai Bahan Pengajaran: Android Application Development as Teaching Material - Wahyuni, Sri; Etfita, Fauzul (Pedagogia : Jurnal Pendidikan, 2020)
The aim of this study was to produce valid and practical android-based learning materials. Research and development (R & D) was used in this study which consists of five stages, namely need analysis, learning design, validation, revison, and trial test. The sample was students who had taken English for Office class. Product assesment questionaire was used in this study as an instruments. Based on the result of the study, the development of android application as learning materials of english for office class fulfilled the eligibility criteria with the result of material expert’s assesment by obtanining a feasiblity of presentation of 86% wit a very valid category, the result of learning practitioner’s evaluation of 99.25% with very valid category, the results of media expert’s evaluation of 90.21% which was categorized as very valid. This reveals that android-based learning materials of english for office subject feasible to use in the learning process.